Rekonstruksi Pengelolaan Komite Sekolah Sebagai Mitra Dalam Peningkatan Mutu Sekolah - Muhamad Faizul Amirudin (Edification Journal : Pendidikan Agama Islam, 2020)
The lack of the role of the school committee in education makes it a school partner to improve its management. Because it is clear in Law number 20 of 2003 concerning National Education System article 56 paragraph 3 that the school council approves in improving the quality of assistance by providing, directives and support for labor, facilities and infrastructure, and supervision of education at the education level. This paper is a literature study that uses documents related to schools and education suppliers as sources of data and analyzed using qualitative descriptive. Reconstruction of the management of the committee through improvements to the planning, organizing, implementing, and evaluating the work program of the school committee and education unit. In addition, training and guidance for school committees also requires building good communication and cooperation between the school committee, the government and other parties. That way it is expected to increase the strategic role of schools in improving the quality of education.